Methanol-Gasoline Fuel Effectiveness Analysis Study - Arif Setyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2022)
This study aims to determine the effect of adding methanol to the methanol-gasoline fuel mixture. It was hoped that the addition of methanol improves the performance of the four-stroke two-wheeled engine, considering that methanol has a better octane rating than gasoline and is more environmentally friendly. The fuels used were pure gasoline and a mixture of methanol-gasoline of M5, M10, M15, M20, M25, and M30. The study used a type of 100cc four-stroke two-wheeled motor fuel. The data collected includes the motor torque, motor power, and fuel consumption. In the research, the M20 fuel produced the highest torque of 7.32 Nm at 5500 rpm. The maximum power obtained from the engine was 6.8 HP at 7000 rpm rotation using M15 fuel. Increasing the concentration of oxygen in the fuel can lead to better combustion quality. The addition of methanol will increase the oxygen concentration in the fuel and cause the calorific value of the fuel mixture to decrease.